1985
DOI: 10.1093/ajcn/41.4.760
|View full text |Cite
|
Sign up to set email alerts
|

The relations between vitamin D2 and D3 in the diet and plasma 250HD2 and 25OHD3 in elderly women in Great Britain

Abstract: Vitamin D2 and D3 intake and plasma 25OHD2 and 25OHD3 were measured in 70 elderly women; 13 living at home and 57 long-stay patients with no access to sunlight. Vitamin D2 intake and plasma 25OHD2 were correlated in the whole group (p less than .005) and vitamin D3 intake and plasma 25OHD3 and total D intake and total 25OHD were significantly correlated (p less than .005) in the patients. In the whole group the plasma 25OHD2 increased by 4.5 nmol/l for every 1 microgram increase in vitamin D2 intake. This was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…However, we had prospective information on vitamin D intake from foods and supplements in our cohort, and adjusting for these covariates did not alter our estimates substantially. While food frequency questionnaires, as used in the current study, have been shown to reflect plasma 25(OH)D levels reasonably well [r = 0.35; [18]], data of elderly people [19, 20] suggest that sun shine exposure is the most important determinant of total 25(OH)D level and therefore, in subjects with low sun exposure, total 25(OH)D level might constitute a better marker of dietary intake of vitamin D. It is therefore possible that, despite the fact that we were able to adjust for a number of important risk factors for osteoporosis including vitamin D intake, there may still be residual confounding for which we were unable to account.…”
Section: Discussionmentioning
confidence: 99%
“…However, we had prospective information on vitamin D intake from foods and supplements in our cohort, and adjusting for these covariates did not alter our estimates substantially. While food frequency questionnaires, as used in the current study, have been shown to reflect plasma 25(OH)D levels reasonably well [r = 0.35; [18]], data of elderly people [19, 20] suggest that sun shine exposure is the most important determinant of total 25(OH)D level and therefore, in subjects with low sun exposure, total 25(OH)D level might constitute a better marker of dietary intake of vitamin D. It is therefore possible that, despite the fact that we were able to adjust for a number of important risk factors for osteoporosis including vitamin D intake, there may still be residual confounding for which we were unable to account.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of dietary vitamin D] is, however, thought to be of only marginal importance, approximately 10%. 10 The serum concentration of total I ,25(OH)2D showed no seasonal variation and the overall data was in agreement with the results of De Luca's' group where they studied adults aged 20-37 years The high individual variations of 1,25(OH)2D we have observed make it difficult to confer any real significance to its change in relation to serum 250HD] to the seasons or number of sunlight hours and suggest single measurements are inappropriate. However, it was interesting that the highest serum concentrations of 1,25(OH)2D observed were only in the winter/spring months and in the summer with the highest 250HD], 1,25(OH 2D) greater than 110 pmollL was not seen.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, a majority of the US population has vitamin D insufficiency with particular subgroups of the population at an even greater risk (e.g. the elderly and those with dark skin) even among otherwise healthy adults ( 7 , 8 ) . Moreover, considerable differences in 25(OH)D serum concentration exist between racial/ethnic groups in the USA, most strikingly between non-Hispanic whites and non-Hispanic blacks.…”
mentioning
confidence: 99%